How can we improve investigation, prevention and treatment for recurrent urinary tract infections – ICI‐RS 2018. (10th December 2019) - Harding, Chris; Rantell, Angela; Cardozo, Linda; Jacobson, Susan Kim; Anding, Ralf; Kirschner‐Hermanns, Ruth; Greenwell, Tamsin; Swamy, Sheela; Malde, Sachin; Abrams, Paul
Abstract: Background: Recurrent urinary tract infection (rUTI) is a chronic condition and has a significant impact on health‐related quality of life. The commonly used definition for rUTI is greater than three episodes in a year or more than two in 6 months. Current diagnostic methods have been used worldwide for over five decades, despite well evidenced criticism. Enhanced culture techniques demonstrate that the microbiome of the bladder is far more complex than previously thought and begs a reappraisal of our current testing. Treatment of rUTI is based on a small number of antibiotic trials with some evidence showing a reduction in the number of positive cultures, but one must be cautious in interpreting the results and weigh against the risk of generation of antimicrobial resistance (AMR). Aim: The International Consultation on Incontinence‐Research Society think tank reviewed the literature with a view to improving investigation, prevention and treatment of rUTI. Methods: A multidisciplinary team of experts were invited to present evidence regarding the current diagnostic methods, recent advances related to bladder biome mapping and current treatment strategies, including antibiotic and nonantibiotic options. Current guidelines regarding antibiotic stewardship and concerns regarding AMR were discussed. Discussion: Outcome of the think tank discussions are summarised with a set of recommendations to inform future research. Particular consideration is given to bacterial survival in the bladder after treatment as well as defects in urothelial barrier function which may play a significant part in the failure to eradicate UTI.